Kelompok Pendukung ASI Moms Support Squad: Inovasi Pemberdayaan Kader Posyandu untuk Mendukung Keberhasilan Menyusui di Depok - Sari, Fitria; Aprillia, Yuna Trisuci; Ulfa, Laila (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
The coverage of exclusive breastfeeding in Indonesia has not yet reached the national target despite the issuance of various regulations, thus requiring community-based strategies to strengthen breastfeeding support. This Community Service Program (PKM) aimed to empower Posyandu cadres through the establishment of the Moms Support Squad as a breastfeeding support group to improve breastfeeding success in Depok City. The program was carried out through several stages, including socialization, training of 25 Posyandu cadres from two Posyandus, provision of educational media (pocket book, flip chart, logbook, diorama, and mannequins), as well as mentoring and evaluation using focus group discussions (FGDs). The results showed significant improvements in knowledge, skills, and caregiving practices. The average knowledge score of cadres increased from 76.14% (pre-test) to 80.91% (post-test), indicating the effectiveness of structured training on exclusive breastfeeding, breastfeeding techniques, and lactation problem-solving. Education delivered by cadres also contributed to improved understanding among pregnant and breastfeeding mothers regarding the benefits of breastfeeding, thereby enhancing their motivation to breastfeed optimally. In terms of skills, cadres demonstrated improved counseling abilities that were more empathetic and solution-oriented. Furthermore, improvements in infant caregiving practices were observed, as mothers began to adopt healthier and more natural parenting based on responsive breastfeeding practices. In conclusion, the Moms Support Squad program effectively enhanced the capacity of Posyandu cadres, improved maternal understanding, and strengthened infant caregiving. This program has the potential to be replicated in other regions as a community-based strategy to support the achievement of national exclusive breastfeeding targets.